2023
DOI: 10.3390/fermentation9110964
|View full text |Cite
|
Sign up to set email alerts
|

Lactic Acid Bacteria in Dairy Foods: Prime Sources of Antimicrobial Compounds

Nooshzad Ahansaz,
Armin Tarrah,
Shadi Pakroo
et al.

Abstract: This review presents an in-depth examination of fermented dairy products, highlighting their significance as rich sources of antimicrobial agents. Through a comprehensive study of microbial activities during fermentation, we identify and discuss the rise of bioactive elements with antimicrobial characteristics. Bacteriocins such as nisin and pediocin play a significant role, as do organic acids such as lactic and acetic acid in providing antimicrobial activity. Challenges, including the enzymes, heat and pH se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 116 publications
0
3
0
Order By: Relevance
“…Challenges in production and purication of selected metabolites: implications for food applications Many reviews have been reported about metabolites' antimicrobial effect resulting from fermentation with lactic acid bacteria. 1,9,[29][30][31][32] However, bacteriocins [33][34][35]37 and phenyllactic acid 6,36 stand out as antimicrobial agents of interest that could be present in fermented foods and fermentates. 27,38,39 Several reports isolate and test the antimicrobial activity of LAB and examine their potential as bacteriocins producers.…”
Section: Antimicrobial Activity Of Fermentatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Challenges in production and purication of selected metabolites: implications for food applications Many reviews have been reported about metabolites' antimicrobial effect resulting from fermentation with lactic acid bacteria. 1,9,[29][30][31][32] However, bacteriocins [33][34][35]37 and phenyllactic acid 6,36 stand out as antimicrobial agents of interest that could be present in fermented foods and fermentates. 27,38,39 Several reports isolate and test the antimicrobial activity of LAB and examine their potential as bacteriocins producers.…”
Section: Antimicrobial Activity Of Fermentatesmentioning
confidence: 99%
“…Many reviews have been reported about metabolites' antimicrobial effect resulting from fermentation with lactic acid bacteria. 1,9,29–32 However, bacteriocins 33–35,37 and phenyllactic acid 6,36 stand out as antimicrobial agents of interest that could be present in fermented foods and fermentates. 27,38,39…”
Section: Antimicrobial Activity Of Fermentatesmentioning
confidence: 99%
“…Probiotic foods are anticipated to comprise around 60%–70% of the functional food industry (Ashaolu, 2021 ; Kołozyn‐Krajewska & Dolatowski, 2012 ). Lactic acid bacteria (LAB) is considered the most significant group of probiotic bacteria used in processed dairy products, particularly in milk, their natural habitat (Ahansaz et al., 2023 ; Delavenne et al., 2012 ; Wouters et al., 2002 ).…”
Section: Introductionmentioning
confidence: 99%